Forest environment and biodiversity / (Acc: 1541) - Singh, M. P. (Mahesh Prasad), 1954-; Vishwakarma, Vinita (Delhi : Daya Pub. House, 1997)
In the Indian context.
Keywords: Forest biodiversity conservation; Sustainable forestry